2017
DOI: 10.1186/s13000-017-0660-1
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell -like carcinoma of the nasal cavity: a case report and review of the literature

Abstract: BackgroundSinonasal renal cell-like carcinoma (SRCLC) is an extremely rare low malignant tumor arising in the sinonasal tract, with histological mimicry of renal cell carcinoma.Case presentationWe present a case of sinonasal renal cell-like carcinoma in a 63-year-old male patient. Computer tomography(CT) scanning revealed a soft tissue mass at the left nasal cavity and choana. Histologically, the predominant tumor architecture was follicular to glandular with intervening fibrous septa. The tumor cells were uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Positivity for S100, DOG1, and SOX10, which are markers of seromucinous differentiation, might depend on the degree of seromucinous differentiation of SNRLCA (33,44). Other reports indicated that TTF-1 was completely negative in SNRCLA (43)(44)(45)(46). We could not find any examinations of CAIX from our review of the literature including our case, but SNRCLA could be differentiated in the final diagnosis because our case was positive for TTF-1 and vimentin.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Positivity for S100, DOG1, and SOX10, which are markers of seromucinous differentiation, might depend on the degree of seromucinous differentiation of SNRLCA (33,44). Other reports indicated that TTF-1 was completely negative in SNRCLA (43)(44)(45)(46). We could not find any examinations of CAIX from our review of the literature including our case, but SNRCLA could be differentiated in the final diagnosis because our case was positive for TTF-1 and vimentin.…”
Section: Discussionmentioning
confidence: 52%
“…Differentiation between TL-LGNPPA and other sinonasal adenocarcinomas [Refer to(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(51)(52)(53)(54)(55)(56)]. …”
mentioning
confidence: 99%
“…On MR imaging, the tumors are heterogeneous to the cortex on T2WI and enhance avidly, similar to renal cell carcinoma. [54][55][56] A key diagnostic criterion is the lack of a concomitant suspicious renal mass (Fig 9).…”
Section: Renal Cell-like Adenocarcinomamentioning
confidence: 99%
“…Their patient was treated with surgical excision alone and was found to have a recurrence 35 months after primary resection. Zhenwei et al reported a patient who underwent surgical excision followed by adjuvant RT and at six months had “no disease progression" [ 10 ]. It is unclear based on the report whether this patient had a persistent disease or had no evidence of disease (NED) at follow-up.…”
Section: Discussionmentioning
confidence: 99%